Synthesis and Cross-Linking of a Benzoxazine-Containing Anthracene Moiety: Thermally Stable Photoluminescent Benzoxazine Resin - Goto, Masahide; Yajima, Tatsuo; Minami, Masaki; Sogawa, Hiromitsu; Sanda, Fumio (Macromolecules, 2020)
A novel benzoxazine derivative, 9,10-bis(6-ethynyl-3-phenyl-3,4-dihydro-1,3-benzoxazine)anthracene (1a), was synthesized by the Sonogashira–Hagihara coupling reaction of 9,10-dibromoanthracene and 6-ethynyl-3-phenyl-3,4-dihydro-1,3-benzoxazine. A CH2Cl2 solution of 1a luminesced with a high quantum yield (Φ = 81%). Compound 1a afforded solvent-insoluble cross-linked polybenzoxazine 1b by the bulk polymerization at 250 °C. Solution polymerization of a dilute solution of 1a at 200 °C afforded solvent-soluble samples, accompanied by a decrease of photoluminescence intensity. The weight loss values of 1a and 1b were 81 and 87%, respectively, under nitrogen at 500 °C. We believe that the present study will lead to thermally stable curing resins whose degree of curing can be estimated with the naked eye by observing the decrease of photoluminescence.